FINANCIAL DISTRESS, LEVERAGE DAN GROWTH OPPORTUNITY TERHADAP ACCOUNTING PRUDENCE DENGAN MENGGUNAKAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Ahmad Zakki Mubarok; Dede Sunaryo; Ahmad Jayanih; Pika Prawesti (Jurnal Comparative: Ekonomi dan Bisnis, 2022)
This study is to determine the effect of financial distress, leverage, growth opportunity on accounting prudence with firm size as a moderating variable in trade, service and investment companies listed on the Indonesia Stock Exchange (BEI). The research time period used is 5 years, namely the period 2017 - 2021. The population of this study includes all trade, service and investment companies listed on the Indonesia Stock Exchange (BEI) for the 2017 – 2021 period with a total of 207 companies. The sampling technique uses purposivesampling technique. Based on the criteria that have been set, 25 companies were obtained with a total of 125 research observation data. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis and Moderated Regression Analysis (MRA) using Eviews 12. The results of this studyindicate thatthe variables of financialdistress, leverage and growth opportunity together have an effect on accounting prudence with firm size as a moderating variable. Partially shows that financial distress has an effect on accounting prudence, while leverage, growth opportunity has no effect on financialdistress. Firm sizeas a moderating variable can moderate the relationship between financial distress and accounting prudence. Meanwhile, Firm size as a moderating variable cannot moderate the relationship between leverage and growth opportunity variables on accounting prudence. Keyword : Accounting Prudence, Financial Distress, Leverage, Growth Opportunity, and Firm Size